Crocin Alleviates Hippocampal Neuron Injury in Rats with Cerebral Ischemia-Reperfusion by Inhibiting JAK2/STAT3 Signaling Pathway - LI Xiaolei; ZHU Haisheng; MA Ruijuan; YAO Li; HU Ke; FENG Lina; WANG Xudong (康复学报)
ObjectiveTo investigate the effect of Crocin (CRO) on rats with hippocampal neuron cerebral ischemia reperfusion (CI/R) injury and explore its potential mechanism.MethodsA total of 144 male SD rats were selected and randomly divided into sham group, model (CI/R) group, CRO low-, medium-, high-dose (CRO-L, CRO-M, CRO-H) group and Nimodipine (NMP) group, with 24 rats in each group. The CI/R rat models were established by suture method. Rats in each group were administered by intrabitoneal injection (ip) once a day starting 7 days before modeling (the CRO-L, CRO-M, CRO-H groups were given 10, 20, 40 mg/kg CRO by ip respectively; the NMP group was given 1 mg/kg NMP by ip; and the sham group and CI/R group were given normal saline 5 mL/kg by ip). After 24 hours of reperfusion, the learning and memory ability of rats was detected by Morris water maze test. The cerebral infarction rate was detected using TTC staining. The neuron pathological changes of hippocampal CA1 and CA3 were observed using HE staining, and the neuronal apoptosis of hippocampal CA1 and CA3 was examined by TUNEL staining. The levels of interleukin (IL)-1β, IL-8, tumor necrosis factor-α (TNF-α) in hippocampal tissue were detected by ELISA. The expression of Janus kinase 2/signal transduction and activator of transcription 3 (JAK2/STAT3) signaling pathway related proteins in hippocampal tissue were detected by Western blot.ResultsCompared with the sham group, the learning and memory ability of the rats in the CI/R group was significantly decreased, and the cerebral infarction rate was significantly increased (P<0.05); the neurons in hippocampal CA1 and CA3 showed pathological changes, such as reduced neuron number, enlarged gaps, vacuolar degeneration, blurred nucleolar border, and inflammatory cell infiltration, and the apoptosis rate was significantly increased (P<0.05); the levels of IL-1β, IL-8, TNF-α in hippocampal tissue were significantly increased (P<0.05); the expression of p-JAK2, p-STAT3, high mobility group protein B1, Bcl-2 associated X protein (Bax), Cleaved Caspase-3 and the ratio of p-JAK2/JAK2, p-STAT3/STAT3, Bax/Bcl-2 were significantly increased, while the expression of Bcl-2 was significantly decreased (P<0.05). Compared with the CI/R group, the learning and memory ability of rats in the CRO-M, CRO-H, and NMP groups was significantly improved, and the cerebral infarction rate was significantly decreased (P<0.05). The neuron pathological changes of hippocampal CA1 and CA3 were significantly improved, and the apoptosis rate was significantly decreased (P<0.05). The levels of IL-1β, IL-8, and TNF-α in hippocampal tissue were significantly decreased (P<0.05). The expression of p-JAK2, p-STAT3, high mobility group protein B1, Bax, Cleaved Caspase-3 and the ratio of p-JAK2/JAK2, p-STAT3/STAT3, and Bax/Bcl-2 were significantly decreased (P<0.05). The above effects of CRO were dose-dependent, and the CRO-H group was significantly superior to the NMP group in terms of learning and memory ability, hippocampal CA1, CA3 neuronal pathological changes and apoptosis rate, inflammatory factor levels, and the expression of JAK2/STAT3 signaling pathway related proteins (P<0.05).ConclusionCRO may play a protective role against hippocampal neuronal injury in CI/R rats by inhibiting the activation of JAK2/STAT3 signaling pathway, reducing inflammation and neuronal apoptosis.